Review—Nanopillar Structure in the Direction of Optical Biosensor On-Chip Integration. Issue 5 (5th May 2021) - Pradana, Arfat; Septiani, Ni Luh Wulan; Dipojono, Hermawan Kresno; Suyatman,; Yuliarto, Brian
Abstract : Biosensors based on nanomaterial have attracted so much interest due to their high-performance potential. Its structure allows the biosensor to have high sensitivity and selectivity. Nanopillar (NPLA) is one class of material with unique properties, especially optical properties. Its unique properties cause it to be the structure that has drawn so much attention recently. The advantages owned by NPLA, including high surface area and its unique optical properties, provide the possibility to build a sensitive layer for a biosensor that is very promising for health and medical applications. This structure also offers low-cost fabrication and can be produced on a mass scale due to its compactness and reliability. Furthermore, NPLA has a high capability to be used as optical biosensors. This article reviews diverse fabrication routes of NPLA structures. Their applications in biomolecular detection, mainly by optical approach, are highlighted. The comparison of the limit of detection of the different kinds of optical biosensors is also presented. The focus of this article lies on the possibilities of NPLA structure integrating into biosensors on-chip.